Strict substrate requirements alongside rapid substrate turnover may indicate an early colonization: A case study of Pleurotus calyptratus (Agaricales, Basidiomycota). (October 2022) - Prylutskyi, Oleh; Yatsiuk, Iryna; Savchenko, Anton; Kit, Maryna; Solodiankin, Oleksii; Schigel, Dmitry
Abstract: Pleurotus calyptratus is a wood-inhabiting oyster mushroom associated with Populus tremula and P. alba . This fungus is rather common in Ukraine, but considered rare in many other European countries. Aiming to find causes for variation in rarity, we conducted habitat mapping and repeated surveys to understand the substrate requirements and fruiting dynamics of P. calyptratus . We showed that fruiting is strictly associated with older trees and early decay stages, and not with physical properties of a tree trunk like volume or position. This timespan of substrate suitability lasts for 1–3 y, determining rapid substrate turnover. We also detected DNA of P. calyptratus in living tissues of visually healthy trees, meaning its latent presence in the hosts, which places the fungus in a position to be a pioneer in a fungal succession. Despite the high spatial and temporal variation in fruiting, five annual surveys demonstrated no significant trends in P. calyptratus population's dynamics, and supported the assumption of random variation in fruiting, driven mostly by dynamics of forest stands. Therefore, we hypothesize that P. calyptratus ' relative abundance in Ukraine is explained by continuous substrate supply from large homogenous aspen stands that are rare in the rest of Europe due to intensive management. Highlights: Pleurotus calyptratus shows yet unexplained differences in rarity across Europe. Repeated fruit body surveys were applied to explore species population dynamics. Latent development of P. calyptratus in young living trees has been proven. P. calyptratus combines both strict requirements and rapid turnover of substrates. Such fruiting pattern can indicate an early colonization strategy for agarics.